2020
DOI: 10.1155/2020/9520309
|View full text |Cite
|
Sign up to set email alerts
|

Selected Metal Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases as Potential Biomarkers for Tubulointerstitial Fibrosis in Children with Unilateral Hydronephrosis

Abstract: Renal tubulointerstitial fibrosis caused by congenital ureteropelvic junction obstruction (UPJO) may lead to the development of obstructive nephropathy (ON) and the impairment of kidney function. Hence, the identification of early biomarkers of this condition might be of assistance in therapeutic decisions. This study evaluates serum and urinary metalloproteinases MMP-1, MMP-2, and MMP-9 and tissue inhibitors of metalloproteinases TIMP-1 and TIMP-2 as potential biomarkers of ON in children with congenital unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These MMPs play primary role in second step of collagen degradation to break down collagen molecules that have been denatured or cleaved by collagenases 80 . In renal fibrosis, there is increasing evidence demonstrating the roles for MMP-9 and MMP-2 in degradation of denatured collagens, fibronectin, laminin, elastin, and vitronectin 81 , 82 . They are also involved in the ECM remodeling 83 , 84 .…”
Section: Discussionmentioning
confidence: 99%
“…These MMPs play primary role in second step of collagen degradation to break down collagen molecules that have been denatured or cleaved by collagenases 80 . In renal fibrosis, there is increasing evidence demonstrating the roles for MMP-9 and MMP-2 in degradation of denatured collagens, fibronectin, laminin, elastin, and vitronectin 81 , 82 . They are also involved in the ECM remodeling 83 , 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, restricted to the deep lateral aspect, solely here the link between the tuft of the defoliating glomerulus and the ascending perforating radiate artery is observed. Unknown is whether the asymmetrical medial and lateral aspects of the shaping nephron are covered by a different composition of extracellular matrix [ 48 ], whether the site-specific installation is controlled by different matrix metalloproteinases [ 49 ] and whether the before described noxae impairing nephrogenesis can eventually cause at this site an imbalance of these regulating enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…When the focus is directed to the numerous enzymes and complex molecular interactions, which build up and degrade the extracellular matrix in the interstitium, it is most probable that the noxae impairing nephrogenesis first target at this balance before they affect the developing nephron as it was shown in the fetuses of diabetic rats [ 49 , 50 ]. Since data for preterm and low birth weight babies is lacking, the task for the future is to elaborate, whether for example the expression of matrix metalloproteinases (MMPs) and related tissue inhibitors (TIMPs) are very first influenced by noxae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMP-2 can enhance the accumulation and production of ECM. [66] Another research [67] reported a positive association between MMP-2 and TGF-β1 urinary excretions, confirming their profibrotic action. Apoptosis and autophagy significantly contribute to developing cellular homeostasis.…”
Section: Dapa and Aunps Impact On Hepatotoxicitymentioning
confidence: 93%